The social origins and expressions of illness. - Singer, Merrill (British medical bulletin, 2004)
This chapter draws on British medical anthropologist Ronald Frankenburg's notion of the 'making social of disease', and his related concepts 'the making of disease' and 'the making individual of disease', to review the biomedical conception of disease from the perspective of medical anthropology. As opposed to the tendency of biomedicine to treat disease as a category in nature, a finite and objective reality discoverable through scientific endeavour, medical anthropology seeks to demonstrate the social origins of both the biomedical conception of disease and the expression of the sicknesses labelled diseases by doctors.
Keywords: Anthropology, Cultural; Attitude of Health Personnel; Attitude to Health; Cultural Evolution; Humans